The genome sequence of the Hoary Bell moth, Eucosma cana (Haworth, 1811) - Boyes, D; Wawman, DC (F1000Research, 2024)
We present a genome assembly from an individual female Eucosma cana (the Hoary Bell; Arthropoda; Insecta; Lepidoptera; Tortricidae). The genome sequence is 580.3 megabases in span. Most of the assembly is scaffolded into 28 chromosomal pseudomolecules, including the Z and W sex chromosomes. The mitochondrial genome has also been assembled and is 16.76 kilobases in length.